Substoichiometric Radiochemical Determination of Cadmium with Sodium Isopropyl Xanthate - Muralikrishna, K.V.; Polaiah, B.; Rangamannar, B. (Asian Journal of Chemistry, 2010)
The present paper brings out a rapid and sensitive substoichiometric radiochemical method in determining the quantity of cadmium by utilising sodium isopropyl xanthate as a reagent. The estimation could be done up to the microgram quantity. Cd complex formed with the reagent was extracted into chloroform by monitoring the value of pH 8 with the ammonia buffers. In the present investigation 2–10 μg of cadmium has been determined from the sample, test solutions with an average error of ±1.76%.